Nanoemulsão como potencial carreador da 4(clorometil)-3-nitro-n-(2-hidroxietil)benzamida: desenvolvimento de formulação e avaliação de parâmetros biológicos in vitro e in vivo. - Jaqueline Aparecida Duarte (2018)
Nitroaromatic derivative 4-(chloromethyl)-3-nitro-N-(2-hydroxiethyl) benzamide (AANC) showed a promissor antitumor activity in solid tumors and reduced systemic toxicity. However, its low solubility in aqueous medium represents a barrier for intravenous (IV) administration. Thus, the aim of this study was to develop nanoemulsions (NE) loaded with AANC to allow its administration by IV route. NE with and without AANC (0.2 and 0.4% w/v) were prepared by the hot melt homogenization method following by ultra-sonication. NE without AANC had a diameter of 93 ± 4 nm, polidispersity index (PI) of 0.25 ± 0.03 and zeta potential of -38 ± 3 mV. The incorporation of AANC signficantly increased the globule diameter, as the concentration was increased from 0.2 to 0.4% w/v. However, the globule mean diameter of the formulations was below 175 nm, and a narrow size distribution with a PI lower than 0.3 was obtained. The concentration of AANC-loaded NE was about 1.66 and 2.50 mg/mL, for 0.2 and 0.4% w/v respectively. There were no significant variation in globule mean diameter, PI, and values zeta potential of the formulations (NE without and with AANC 0.4% w/v over 28 days of evaluation. However, significant reduction in the AANC concentration was also observed after 14 days of storage. Next, the cytotoxicity of the free AANC and the NE-AANC was evaluated by MTT assay against MDA-MB-231 cells (human breast adenocarcinoma). IC50 values obtained for free AANC (23.9 ± 3.0 μM) and NE-AANC (24.1 ± 0.4 μM) were similar, showing that the cytotoxicity of AANC was not affected by loading in NE. In order to evaluate the in vivo behavior of free AANC and NE-AANC, pharmacokinetic and biodistribution studies in murine experimental models were conducted. Similar half-life time for free AANC and NE-AANC was obtained. Biodistribution data and scintigraphic images showed a pronounced uptake in the liver, kidneys and intestine and significant accumulation in the tumor region. Tumor-to-muscle ratio was significantly higher for NE-AANC than free AANC suggesting greater specificity for the tumor region. Therefore, NE formulation can be a good strategy to the association of the AANC, and to allow its intravenous administration.